AGE AND GROWTH OF THE JUVENILES OF KOTH OTOLITHOIDES BRUNNEUS (DAY) IN BOMBAY WATERS - Jayaprakash, A A (Indian Journal of Fisheries, 2011)
Otolithoides brunneus (Day), locally called ’Koth’, occurring along the Bombay and Saurashtra waters, is a sciaenid, growing to a size of over 160 cm and supporting a fishery of some importance (Jayaraman et al 1959, Bhatt et al 1967, Rao et al 1966, 1972). Karandikar and Thakur (1951) studied the anatomy of ’Koth’. Kutty (1961, 1967) studied the age and growth of this species by using the scales and otoliths. He also made a brief report on certain other aspects of its biology